Photoprotection and chloroplast regulation in the green algae Chlamydomonas reinhardtii - Cantrell, Michael, author; Peers, Graham, advisor; Pilon, Marinus, committee member; Reddy, A. S. N., committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2019)
Absorbed light energy in excess of a cell's photosynthetic capacity can lead to production of reactive oxygen species (ROS) causing cell damage and death. Plants and algae have evolved conserved photoprotective responses that, at the level of light harvesting, are collectively measured as non-photochemical quenching (NPQ) of chlorophyll fluorescence. The major components of NPQ are thermal dissipation of excess light energy (excitation dependent quenching, qE), the migration of antenna complexes from PSII to PSI (state transitions, qT) and inactivation of PSII by damage (photoinhibition, qI). Excess reductant generated during light harvesting can also be dissipated by auxiliary electron transport (AET). The following dissertation aimed to characterize the role of qE in acclimation to saturating and sinusoidal light regimes in the model green algae Chlamydomonas reinhardtii, to characterize potential energy dissipating mechanisms that may occur in absence of qE and identify factors regulating the expression of the chloroplast encoded photosystem I subunit, psaA, using a forward genetic screen. In chapter 2 I show that the qE mutant, npq4lhcsr1, displays decreased growth under a sinusoidal light regime mimicking natural oscillations in irradiance. This reduction in growth rate occurs without a significant impact on carbon accumulation, accumulation of oxidized lipids or impairment of photosynthetic rate. We hypothesized that this was due to increased consumption of excess energy by AET pathways and the results of this investigation are presented in chapter 3. We found that absence of qE in Chlamydomonas did not significantly impact AET associated with light dependent oxygen consumption. The npq4lhcsr1 mutant instead appears to experience less acceptor side limitation downstream of Photosystem I and have a greater capacity for state transitions. This in the absence of any evidence for increased light dependent oxygen consumption in the npq4lhcsr1 mutant indicates that Chlamydomonas compensate for the absence of qE by increasing cyclic electron transport around Photosystem I, which generates additional ATP at the cost of NADPH. In my final chapter I use a positive selectable marker to generate a library of 400 putative psaA mutants, present preliminary flanking sequence characterization for 29 of these mutants and discuss possible roles they may be playing in psaA regulation. Together these chapters expand our understating of the role of qE in long term acclimation to saturating and sinusoidal light regimes and provide a library of putative chloroplast regulatory mutants that, with further characterization, will refine our understanding of chloroplast genome regulation in green algae.
Keywords: membrane inlet mass spectrometry; photosynthesis; non-photochemical quenching; excitation dependent quenching